Magnetic flux control in an urban distribution network based on load optimisation. Issue 2 (28th May 2021) - Lei, He; Zheng, Xu; Sang, Zixia; Fang, Rengcun; Yan, Jiong; Wang, Yingxiang; Du, Zhi; Yang, Dongjun; Xu, Jingyou; Wu, Lei
Abstract : This paper proposes a control method for eliminating direct current (DC) flux from the isolation transformer of a customer service device to avoid magnetic saturation. The method is characterised by injecting zero compensation voltage during a designed time. The period during which no compensation voltage is injected is minimised by adjusting the normal compensation time in the initial stage. For a customer service device, such as a dynamic voltage restorer, the reverse turn-off voltage will introduce extra initial flux. The calculation process based on a trigonometric function also takes into account the effects of the initial flux. The experimental results verify the proposed method to prevent DC flux to the isolation transformer.